Graphene‐based Oxygen Reduction Electrodes for Low Temperature Solid Oxide Fuel Cells. Issue 3 (27th April 2017) - Jee, Y.; Karimaghaloo, A.; Andrade, A. Macedo; Moon, H.; Li, Y.; Han, J.‐W.; Ji, S.; Ishihara, H.; Su, P.‐C.; Cha, S. W.; Tung, V. C.; Lee, M. H.
Abstract: In this report, we present a study of using nitrogen‐doped graphene as the air electrode of low temperature solid oxide fuel cells (LT‐SOFCs) operating at 350 °C or lower. Three graphene derivatives were prepared through hydrothermal reactions and their electrochemical performance and material properties were characterized in the temperature range of 225–350 °C in atmospheric air. Nitrogen‐doped graphene was found to exhibit a decent air electrode performance comparable to a porous Pt electrode aged for 8 h at 350 °C, but only for a limited time. After ∼10 h of operation at 350 °C, the electrode performance degraded significantly due to carbon oxidation. However, alternative routes of synthesizing/doping graphene derivatives are expected to improve the viability of using these materials as a practical high temperature air electrode.